Soft rot on the stems of Zamioculcas zamiifolia caused by Sclerotium rolfsii - Mariana Cunha Stutz (Ornamental Horticulture, 2019)
Zamioculcas zamiifolia (Araceae) is one of the most widely grown exotic species in Brazil as ornamental plants and in landscape design. Despite tolerating transport and being well adapted to low-light environments, this ornamental is attacked by different pathogens. Thus, the aim was to detect and identify the pathogen that causes stem rot in commercial Z. zamiifolia crops. Z. zamiifolia plants exhibiting stem rot symptoms were sent for phytosanitary diagnosis. In a culture medium, the fungal isolate obtained (SR-001) displayed the following morphological characteristics: cotton-like aerial mycelium, septate hyaline hyphae with no spore production, and the formation of small brown spherical sclerotia. To confirm pathogenicity, Z. zamiifolia plants were inoculated with the SR-001 isolate and, after fifteen days, the fungus was re-isolated when the same rot symptoms emerged. The SR-001 isolate was identified as Sclerotium rolfsii and its representative sequence was deposited in GenBank (Access MG694322). This fungal isolate has not been associated with diseases in Z. zamiifolia in Brazil, and this is the first report of the fungus infecting this ornamental plant species in a cultivated area.